Barriers to energy efficiency and the uptake of green revolving funds in Canadian universities. Issue 2 (2nd March 2015) - Maiorano, John; Savan, Beth
Abstract : Purpose: – The purpose of this paper is to investigate the barriers to the implementation of energy efficiency projects in Canadian universities, including access to capital, bounded rationality, hidden costs, imperfect information, risk and split incentives. Methods to address these barriers are investigated, including evaluating the efficacy of revolving funds. Design/methodology/approach: – Senior administrators of 15 Canadian universities were interviewed, making use of both structured and open-ended questions. As university executives and senior technical directors are responsible for investment in energy efficiency at Canadian universities, these individuals were the focus of our study. Findings: – The results offer a curious contradiction. While "Access to Capital" was found to be the largest barrier to energy efficiency in Canadian universities, and while respondents agreed that green revolving funds are both an effective method to address these capital funding constraints, and may be an effective method to implement energy conservation projects at their university, only 2 out of the 15 universities interviewed and 7 out of the 98 universities in Canada currently make use of a green revolving fund. A general reluctance at Canadian universities to formalize processes to prioritize energy efficiency limits the associated benefits of mechanisms such as revolving funds to institutionalize energy efficiency and reduce long-term energy use. Practical implications: – To provide insights into barriers to energy efficiency in universities and methods to address them, including the efficacy of revolving funds. Originality/value: – This research is one of the first to investigate the efficacy of revolving funds to confront barriers to energy efficiency. The findings, implications and recommendations are valuable to organizations, university administrators, researchers and practitioners implementing energy efficiency measures.